2019
DOI: 10.1017/s0261143019000102
|View full text |Cite
|
Sign up to set email alerts
|

Religion and heavy metal music in Indonesia

Abstract: We trace the history of Indonesian Islamic metal bands, including Purgatory, Tengkorak and Kodusa, and the One Finger Movement that revolved around these bands (centred mainly on Jakarta). We look at the differences in symbols, heroes, rituals and values between One Finger Movement bands and the Bandung (Indonesia) secular Death Metal scene. We also study Bandung Death Metal band Saffar, which was known for its Islamic lyrics on its debut album but which has been for a few years in something of a limbo owing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…Step, Super Kid, Terncem, and AKA. Although the first rock record label, Logiss Records, was formed in the 80s, the scene's foundation of metal bands established in the mid to late 1990s, and the scene had grown to approximately its present size by 2011 (James & Walsh, 2019). Nowadays, Indonesia is a hotbed of heavy metal having more than 1,500 heavy metal bands across the archipelago, the highest number of head-slamming, ear-splitting heavy metal bands in Asia (Mutia, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Step, Super Kid, Terncem, and AKA. Although the first rock record label, Logiss Records, was formed in the 80s, the scene's foundation of metal bands established in the mid to late 1990s, and the scene had grown to approximately its present size by 2011 (James & Walsh, 2019). Nowadays, Indonesia is a hotbed of heavy metal having more than 1,500 heavy metal bands across the archipelago, the highest number of head-slamming, ear-splitting heavy metal bands in Asia (Mutia, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A similar reaction applies to the very public and hegemonic roles on how Islamic belief and practice play in Indonesian life. Metalheads want a safe place to pursue their subcultural interests and practices, free from the influences of the broader society (James & Walsh, 2019). In Islamic tradition in Indonesia, music which expectedly moves people harts closer to both God and Messengers are usually allowed regardless of its genres (Harnish & Rasmusen, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, it was under challenge from the sovereign consumer ideal. In my research with Rex Walsh on Bandung Death Metal, beginning in 2011 (James and Walsh 2015, 2018, 2019), we too found that many musicians and fans thought that black-T-shirts-plus-loud-music signifies underground values, by definition, and although many musicians are social and political activists in their own ways (such as Man of Jasad and Butche of The Cruel), many are not. Many just enjoy the soundscapes and the sociality – there is nothing wrong with that, but is it pemuda ?…”
mentioning
confidence: 96%
“…konservatif. Kemudian oleh James dan Walsh (James & Walsh., 2019), yang mencoba mengidentifikasi metal Islam di Indonesia, menjadi dua kelompok, konservatif dan sekuler. Berbeda dengan dua penelitian di atas, tulisan ini menggunakan pendekatan budaya untuk memahami hibridisasi metal Islam di Indonesia, terutama bagaimana selama ini Islam diartikulasikan di Indonesia, sehingga penelitian ini memiliki kesamaan dengan melihat metal Islam sebagai fenomena hibrid, tetapi yang membedakannya dalam penelitian ini penulis melihat ada sikap kosmopolitanisme yang melatarbelakangi hibridisasi metal Islam.…”
unclassified